KEJADIAN PENYAKIT RADANG PARU Pneumonia DAN ENTERISTIS PADA BEKANTAN Nasalis larvatus DI KEBUN BINATANG SURABAYA - I Komang Wiarsa Sardjana (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
Incidence of Pneumonia and Enteistis on the proboscis monkey as Bekantan (Nasalis larvatus) was done at the Surabaya Zoological Gardens. Sixty one proboscis monkeys were evacuated from their habitat in Kaget island, south Kalimantan because of the habitat destruction. Thirty seven Proboscis monkeys were dead of Pneumonia and Enteritis by worms parasite infection. The preventive and treatment program with anti-biotherapy, liquid pertusion and anthelmentica have already been done as well as nutrition quality improvement and living environment to save the animals at Surabaya Zoological Gardens.